Proximate Analysis and Organoleptic Acceptance of Snack Bar Based on Green Pea Flour (Vigna Radita) and Red Pea Flour (Phaseolus Vulgaris L) - Lestari, Serly; Yuliantini, Emy; Suryani, Desri (Jurnal Ilmiah Kesehatan (JIKA), 2024)
Snack bars are snacks in the form of bars that are produced from various food components with added nutrients such as whole grains, dried fruit, or nuts. The aim of the research was to determine the proximate levels and test the organoleptic acceptability of snack bars using a completely randomized design (CRD) with treatment, added green beans and red beans F1 (100:25) F2 (62,5:62,5), F3 (25: 100). Organoleptic tests were carried out with 30 training panelists. The data were analyzed using the Kruskall Wallis test and continued with Mann Whitney. The results on the proximate level test was found that the highest water content value was in formula 1 (15,509%), the ash content in formula 1 was 2,547%, and the fat content in formula 1 was 22,751. Meanwhile, the highest protein content was in formula 3 (25,68%), carbohydrate content was 48,023% and the highest food fiber content was in formula 1 (17,512%). Result of proximate analysis and organoleptic tests was Formula 1 (100g green bean flour and 25g red bean flour) as the best product. The resulting formula can be a nutritious alternative as snack, with high level of protein, carbohydrates and fiber. The implications of developing a snack bar is not only nutritious, but also tastes good. This opens up opportunities to diversify healthier snack products by utilizing local resources.